Individual and Interactive Effects of Ocean Warming and Acidification on Adult Favites colemani - Tañedo, Mikhael Clotilde S.; Villanueva, Ronald D.; Torres, Andrew F.; Ravago-Gotanco, Rachel; San Diego-McGlone, Maria Lourdes (Frontiers in Marine Science, 2021)
Tropical coral reefs are threatened by local-scale stressors that are exacerbated by global ocean warming and acidification from the post-industrial increase of atmospheric CO2 levels. Despite their observed decline in the past four decades, little is known on how Philippine coral reefs will respond to ocean warming and acidification. This study explored individual and synergistic effects of present-day (pH 8.0, 28°C) and near-future (pH 7.7, 32°C) scenarios of ocean temperature and pH on the adult Favites colemani, a common massive reef-building coral in Bolinao-Anda, Philippines. Changes in seawater temperature drive the physiological responses of F. colemani, whereas changes in pH create an additive effect on survival, growth, and photosynthetic efficiency. Under near-future scenarios, F. colemani showed sustained photosynthetic competency despite the decline in growth rate and zooxanthellae density. F. colemani exhibited specificity with the Cladocopium clade C3u. This coral experienced lower growth rates but survived projected near-future ocean warming and acidification scenarios. Its pH-thermal stress threshold is possibly a consequence of acclimation and adaptation to local environmental conditions and past bleaching events. This research highlights the importance of examining the susceptibility and resilience of Philippine corals to climate-driven stressors for future conservation and restoration efforts in the changing ocean.